Analysis of herbary samples of dracocephalum l. trees distributed in uzbekistan - Abdullayeva Nilufar Sag‘dullayevna; Unarova Nozima (International Journal on Orange Technologies, 2021)
The article describes the species of Dracocephalum L., distributed in the flora of Uzbekistan,the National Herbarium (TASH) of the institute of Botany of the Academy of Sciences of Uzbekistan and they analyzed the samples stored in the herbarium fund of the Moscow State University Lomonosov (MW). Accordingly, 2174 herbarium specimens collected from Central Asia and Uzbekistan were collected in the (MW) herbarium fund, and 1738 herbarium specimens of 22 species were critically analyzed in the TASH fund. An electronic database was linked based on the study.